Plaque Assay for Q Fever and Scrub Typhus Rickettsiae - McDade, Joseph E. (1970)
The plaque assay procedure developed for spotted fever and typhus group rickettsiae is also appropriate for scrub typhus and Q fever rickettsiae. The plaque titers of suspensions of Rickettsia tsutsugamushi and Coxiella burnetii compared favorably with end points obtained by titrations in mice.